Clinical Prevention Strategies of Rebound Pain Phenomenon After Peripheral Nerve Block : A Narrative Review - Made Ricky Catur Purnama; I Gusti Ngurah Mahaalit Aribawa (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Peripheral nerve block (PNB) is a key technique in perioperative pain management, effectively reducing pain intensity and opioid consumption. However, the phenomenon of rebound pain, defined as a significant increase in pain after the resolution of nerve block effects, has emerged as an increasingly recognized clinical challenge. This review aims to evaluate the pathophysiology, risk factors, clinical impact, and prevention strategies of rebound pain. A narrative review approach was employed through literature searches in PubMed, Scopus, and Google Scholar using keywords related to rebound pain and peripheral nerve block. Included articles comprised clinical studies, systematic reviews, and meta-analyses published within the last five years and relevant to the topic. The literature was critically analyzed and synthesized narratively. Rebound pain typically occurs within 12–24 hours postoperatively and is associated with peripheral and central sensitization, tissue inflammation, and increased neuronal excitability. Risk factors include younger age, orthopedic procedures, use of single-shot blocks, and inadequate multimodal analgesia. Clinical consequences include sleep disturbances, increased opioid consumption, and reduced patient satisfaction. Prevention strategies involve patient education, administration of analgesics prior to block resolution, use of dexamethasone, and continuous nerve block techniques. With an evidence-based approach, the benefits of PNB can be optimized without increasing the risk of rebound pain, thereby improving the quality of perioperative pain management. Keywords: Peripheral Nerve Block, Rebound Pain, Multimodal Analgesia, Dexamethasone, Postoperative Pain.